2017
DOI: 10.1111/pcn.12562
|View full text |Cite
|
Sign up to set email alerts
|

Optimal cut‐off score of the Edinburgh Postnatal Depression Scale for major depressive episode during pregnancy in Japan

Abstract: To our knowledge, this is the first study to clarify the optimal EPDS cut-off score in the second trimester for Japan. This finding will be helpful for appropriate screening for antenatal depression in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 29 publications
3
42
1
1
Order By: Relevance
“…Prevalence of depression in the perinatal period has been reported as 7% to 25% . In these previous studies, DSM‐4 and research diagnostic criteria were used as the diagnostic criteria for depression, and the time point of diagnosis ranged from the pregnancy period to several months after delivery; therefore, the prevalence of PPD under certain conditions is not clear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prevalence of depression in the perinatal period has been reported as 7% to 25% . In these previous studies, DSM‐4 and research diagnostic criteria were used as the diagnostic criteria for depression, and the time point of diagnosis ranged from the pregnancy period to several months after delivery; therefore, the prevalence of PPD under certain conditions is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a report that major depressive disorder was found in 20 out of 210 Japanese pregnant women by Usuda et al ., the ratio of PPD to non‐PPD was assumed to be 1 to 9. Under the conditions of area under the curve (AUC) 0.8, power 0.90, case control ratio 1:9, and α 0.05, sample size required for the ROC analysis was estimated to be 80 in total (eight cases of PPD and 72 cases of non‐PPD).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Okano et al reported that the appropriate cutoff point for detecting PPD was 9 or higher, with 75% sensitivity and 93% specificity (Yamaoka et al 2016;Muchanga et al 2017), whereas 12 or higher is generally used as the cutoff point worldwide (Cox et al 1987). A recent study on Japanese women has shown the optimal cutoff of EPDS score for major depressive episode during pregnancy as 12 (Usuda et al 2017). We, therefore, used both cutoff points > 9, and > 12, in this study.…”
Section: Variablesmentioning
confidence: 99%
“…This questionnaire has been validated against the Research Diagnostic Criteria for depression with a sensitivity of 86% and a specificity of 78% (Cox & Holden, 2003). Total scores were dichotomised using a cut-point of 10; a score of ≥ 10 indicated postpartum depressive symptoms (Usuda, Nishi, Okazaki, Makino, & Sano, 2017).…”
Section: Ijphcsmentioning
confidence: 99%